Women and science : 17th century to present : pioneers, activists and protagonists - Andréolle, Donna Spalding; Molinari, Véronique (Cambridge Scholars, 2011)
If women's interest and participation in the advancement of science has a long history, the academic study of their contributions is a far more recent phenomenon, to be placed in the wake of "second wave" feminism in the 1970s and the advent of women's studies which have, since then, given impetus to research on female figures in specific fields or, more generally speaking, on women's battles to gain access to knowledge, education and recognition in the scientific world. These studies-while p ...